EVALUATION OF EFFICACY AND SAFETY OF RENOMET, A POLYHERBAL FORMULATION IN THE TREATMENT OF UROLITHIASIS: A DOUBLE BLIND RANDOMIZED STUDY (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Nephrolithiasis is one of the most commonly occurring disorders in India. Although this disorder is seen in any age group, young and middles aged individuals are the most common sufferers. The treatment of nephrolithiasis is mostly diuretics or surgical procedure. However, commonest complaint of patients where the stones have been removed surgically is recurrence. Therefore a need was felt to evaluate the efficacy of Renomet, a poly herbal product in the treatment of nephrolithiasis. Seventy four patients between 35-60 years of age and fulfilling inclusion criteria were included in the trial. All the patients had multiple stones up to 9 mm in size and had past history of renal stones surgically removed. They were divided in to two groups after obtaining the informed consent and administered either Renomet or a commercially available herbal formulation at the dose of 1 tablet twice daily for 6 weeks. Patients were asked to report for any side effect during the treatment period. At the end of the trial, patients in the Renomet treated group were found to be symptom free and about 98% of them had passed the stone. Where as in the herbal supplement (CAHP) group only 68% patients had passed stones. The average size of the stone in group A and B at the time of recruitment were 8.88 ± 0.26 and 7.10 ± 0.88 respectively. After 6 weeks of treatment with Renomet Group A), dysuria and hematuria improved in all (100%) and pain abdomen improved in 98.6% cases. In group B, after 6 weeks of treatment with CAHP, pain abdomen was still present in 8.7%, hematuria in 3.26% and dysuria in 14.99% of cases. The average size of the stone reduced to 4.1 ± 0.22 in group A, while in group B the size reduced to 5.56 ± 0.43.